Investment Cash Flow Sensitivity and Effect of Managers' Ownership: Difference between Central Owned and Private Owned Companies in China - Ding, Yuanyao; Qian, Xu (International Journal of Economics and Financial Issues, 2014)
Based on panel data of the listed companies in China’s stock market A during a period of year 2007-2010, we made an empirical study on what drives the investment cash flow sensitivity and the effect of management’s ownership and both their differences between the central state owned companies and the non-state owned companies as well. The sensitivity of investment to internal cash flow in China’s central state-owned companies can be explained by “hypothesis of free cash flow”. It is the cost of agency that causes over-investment behaviors, and the management’s ownership appears significant enhancement effect rather than entrenchment effect. However, the sensitivity of investment to internal cash flow in China’s non-state owned companies supports the explanation of “hypothesis of financial constraints”. Asymmetrical information causes under-investment behaviors of the firms. In the mean while, the entrenchment effect of manages’ ownership dominates the enhancement effect in non-state owned companies. Keywords: Internal Cash Flow; External Financial Constraints; Entrenchment Effect. JEL Classifications: G01; G31; G32